Noninvasive imaging diagnosis of sinusoidal obstruction syndrome: a pictorial review - Zhang, Yun (Insights Imaging, 2019)
Sinusoidal obstruction syndrome (SOS) is a rare liver disorder due to hepatic vascular injury. Its rapid and accurate diagnosis is crucial for patient survival. SOS is often established clinically, based on Baltimore, modified Seattle, or European Society for Blood and Marrow Transplantation (EBMT) criteria. Unfortunately, such criteria are not highly specificity and fail to provide a timely, reliable differential diagnosis. The use of noninvasive imaging techniques, such as ultrasound (US), computed tomography (CT), magnetic resonance imaging (MRI), and fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT), has recently grown in this setting, some key imaging features offering diagnostic improvement. This review provides a synopsis of current noninvasive imaging techniques used for this purpose, summarizing accurate and reliable diagnostic features of SOS.